New and continuing physician-based outpatient mental health care among children and adolescents during the COVID-19 pandemic in Ontario, Canada: a population-based study - Toulany, Alene; Vigod, Simone; Kurdyak, Paul; Stukel, Therese A.; Strauss, Rachel; Fu, Longdi; Guttmann, Astrid; Guan, Jun; Cohen, Eyal; Chiu, Maria; Hepburn, Charlotte Moore; Moran, Kimberly; et al. (Frontiers in Psychiatry, 2023)
Objective: To assess physician-based mental health care utilization during the COVID-19 pandemic among children and adolescents new to care and those already engaged with mental health services, and to evaluate differences by sociodemographic factors. Materials and Methods: We performed a population-based repeated cross-sectional study using linked health and administrative databases in Ontario, Canada among all children and adolescents 3-17 years. We examined outpatient visit rates per 1000 population for mental health concerns for those new to care (no physician-based mental healthcare for ≥1 year) and those with continuing care needs (any physician-based mental healthcare <1 year) following onset of the pandemic. Results: Among 2.5 million children and adolescents (48.7% female, mean age 10.1±4.3 years), expected monthly mental health outpatient visits were 1.5/1000 for those new to mental health care and 5.4/1000 for those already engaged in care. Following onset of the pandemic, visit rates for both groups were above expected (adjusted rate ratio (aRR) 1.22, 95% CI 1.17, 1.27; aRR 1.10, 95% CI 1.07, 1.12) for new and continuing care respectively. The greatest increase above expected was among females (new: aRR 1.33, 95% CI 1.25, 1.42; continuing: aRR 1.22 95% CI 1.17, 1.26) and adolescents ages 13-17 years (new: aRR 1.31, 95% CI 1.27, 1.34; continuing: aRR 1.15 95% CI 1.13, 1.17). Mood and anxiety concerns were prominent among those new to care. Conclusion(s): In the 18-months following onset of the pandemic, outpatient mental health care utilization increased for those with new and continuing care needs, especially among females and adolescents.